(untitled) (Indian Journal of Child Health, 2019)
Background: Longlines are commonly used in neonatal practice in the West. Its correct placement is important to avoid complications such as extravasation of fluids into pleural, pericardial, and subcutaneous compartments which may prove fatal in some neonates. Objective: The objective of the study was to review the indications, insertion characteristics, post-insertion care, and complications of longlines in sick neonates and to emphasize its use in managing extremely low birth weight (ELBW) and very low birth weight (VLBW) babies at special newborn care unit (SNCU) level. Materials and Methods: A prospective cross-sectional observational study of all longline insertions during January 2014–June 2019 in the SNCU of a medical college of the Eastern State was undertaken. The indications, number of attempts at insertion, procedure time, and duration of longline stay, number of dressing change, complications and cause of removal were noted and the study variables were analyzed. Results: A total of 312 neonates were included; of them, 140 were ELBW and 172 were VLBW babies. Successful insertion of longlines in the first attempt occurred in 294 (94.23%) neonates. 16 (5.12%) neonates required second attempt, while only 2 (0.64%) required third attempt. The average time taken for the procedure was 30 min–1 h and average duration of longline stay was 18.3 days. Low complication rates were recorded such as occlusion in 24 (7.69%) cases, dislodgement in 3 (0.96%), migration in 4 (1.28%), sepsis in 15 (4.8%), and profuse bleeding at insertion site in 1 (0.32%) neonates. Conclusion: Longline is a safe, effective, and reliable method of providing prolonged IV access in sick small neonates, especially ELBW and VLBW babies. Longlines can be recommended for routine use at SNCU level.